2021
DOI: 10.3390/ijerph18178914
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Diabetes Family Conflict and Parental Conflict on Problem Recognition in Illness Self-Management among Individuals with Type 1 Diabetes Mellitus

Abstract: We investigated the relationship between diabetes family conflict and parental conflict on problem recognition in illness self-management (PRISM) among individuals with type 1 diabetes mellitus (T1DM). We employed a descriptive research design. Participants were 243 individuals with T1DM who completed online questionnaires. Data were analyzed with descriptive statistics, correlations, and multiple regression analyses. Results revealed that barriers were felt in all areas (understanding and organizing care, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Moreover, patients with glycated hemoglobin levels ≥ 8.0% show a higher degree of depression than those with lower glycated hemoglobin. This finding is consistent with that of a previous study [ 29 ], which found that parents’ quality of life was significantly lower when they did not receive education on diabetes, had only one child, or their child with the disease was the oldest. This finding suggests that education on diabetes is essential.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, patients with glycated hemoglobin levels ≥ 8.0% show a higher degree of depression than those with lower glycated hemoglobin. This finding is consistent with that of a previous study [ 29 ], which found that parents’ quality of life was significantly lower when they did not receive education on diabetes, had only one child, or their child with the disease was the oldest. This finding suggests that education on diabetes is essential.…”
Section: Discussionsupporting
confidence: 93%
“…Involving the family as the closest source of care is included in the FCS intervention. Good self-management of people with diabetes will be well described by the most effective family support (Cho & Kim, 2021). Family members must participate in every care activity to actively manage DM risk factors experienced by another family member (Vinsalia & Handajani, 2021).…”
Section: Discussionmentioning
confidence: 99%